Spectroscopic, antiproliferative and antiradical properties of Cu(II), Ni(II), and Zn(II) complexes with amino acid based Schiff bases - Genc, Zuhal Karagoz; Selcuk, Sibel; Sandal, Suleyman; Colak, Naki; Keser, Serhat; Sekerci, Memet; Karatepe, Mustafa (Springer Birkhauser, 2014)
Novel six Cu(II), Ni(II), and Zn(II) complexes with Schiff bases derived from 4-aminobenzoic acid with terephtaldehyde and amino acids (glycine, beta-alanine). Structures have been proposed from elemental analysis, UV-Vis, IR, NMR, TGA, DTA, and magnetic measurements. Spectroscopic studies suggest that coordination occurs through azomethine nitrogen, hydroxyl group, and carbonyl oxygen of the ligands to the metal ions. The elemental analyses of the complexes where L is Schiff base ligands, are confined to the stoichiometry of the type M2L2(CH3COO)(2) [M = Cu(II)]; and M2L(CH3COO)(2) [M = Ni(II) and Zn(II)]. The cytotoxicity activities of the compounds against human breast carcinoma MCF-7 cell line have been studied. Ligands and their Zn(II) compounds inhibited cell proliferation of MCF-7 cancer cell lines in a dose- and time-dependent manner. The free radical scavenging activity was measured by 1,1-diphenyl-2-picryl-hydrazil. Our results show that the synthesized compounds induced oxidative damage by increasing the lipid peroxidation in yeast since MDA formation was increased, and it could be concluded that the synthesized compounds caused oxidative stress. In addition, the antioxidant activities of the synthesized compounds were very much lower than those of standard antioxidants.
Keywords: Spectroscopy; Schiff base; Antiproliferative activity; DPPH